2020
DOI: 10.1007/s43152-020-00018-5
|View full text |Cite
|
Sign up to set email alerts
|

Interface of DNA Repair and Metabolism

Abstract: Purpose of Review DNA is naturally very unstable and several agents are capable of damaging and altering its structure, thus leading to several negative consequences. Therefore, this review seeks to better understand the relationship between different DNA repair mechanisms and metabolic pathways, and how such a relationship can influence the outcome of different human inflammatory diseases. Recent Findings Studies have shown that factors involved in DNA repair are also involved in the regulation of cellular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 151 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…Transcriptomic changes were similar to the proteomic changes, in which the abundance of several metabolic proteins was modified. The association between DDR and metabolism is well known [ 40 , 41 ]. It has been previously shown that growth factors govern metabolism, while metabolism is a factor that drives the cell cycle and proliferation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic changes were similar to the proteomic changes, in which the abundance of several metabolic proteins was modified. The association between DDR and metabolism is well known [ 40 , 41 ]. It has been previously shown that growth factors govern metabolism, while metabolism is a factor that drives the cell cycle and proliferation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%